Directed Lithiation of N′-[2-(4-Methoxyphenyl)ethyl]-N,N-dimethylurea and tert-Butyl [2-(4-Methoxyphenyl)ethyl]carbamate - Smith, Keith; El-Hiti, Gamal A.; Alshammari, Mohammed B. (Synthesis, 2014)
N′-[2-(4-Methoxyphenyl)ethyl]-N,N-dimethylurea and tert-butyl [2-(4-methoxyphenyl)ethyl]carbamate are doubly lithiated on the nitrogen and ortho to the directing metalating group at –20 to 0 °C with three mole equivalents of n-BuLi in anhydrous THF. Reactions of the dilithium reagents produced in situ with various electrophiles give high yields of the corresponding substituted products. In the case of the urea, side-products due to lithiation and substitution on one of the methyl groups of the urea unit are obtained in low yields (0–17%).
Keywords: directed lithiation; side-chain lithiation; N′-[2-(4-methoxyphenyl)ethyl]-N,N-dimethylurea; tert-butyl [2-(4-methoxyphenyl)ethyl]carbamate; electrophile